Nilai Kultural dalam Tortor Ija Juma Tidahan Sebagai Bentuk Repitalisasi Budaya Simalungun Yang Hampir Pudar - Putri, Sri Lestari; Nathan, Nixon Randy; Simorangkir, Krishna Stevanie; Ambalegin, Ambalegin (Yayasan Tri Edukasi Ilmiah, 2025)
Tortor Ija Juma Tidahan is a traditional Simalungun dance rich in cultural values and philosophical meanings. Over time, the existence of this dance has begun to fade amidst the current of modernization. This study aims to analyze the cultural values in Tortor Ija Juma Tidahan as a form of revitalization of the almost faded Simalungun culture, using Peirce's semiotic approach (1931). In this analysis, dance elements such as movements, music, clothing, and visual symbols are categorized into icons, indices, and symbols. The results show that dance movements function as indices that reflect the close relationship of the Simalungun people with nature and farming activities, while music and clothing act as icons and symbols that represent cultural identity and spiritual values. Although this dance has experienced a shift in function from sacred rituals to entertainment, its cultural meaning still persists. This study concludes that the revitalization of Tortor Ija Juma Tidahan can be done through adaptation to modern media, cultural education among the younger generation, and integration into traditional activities and cultural festivals as an effort to maintain the existence and meaning of this dance in the era of globalization.